Implications for Greenhouse Gas Emission Reductions and Economics of a Changing Agricultural Mosaic in the Sacramento–San Joaquin Delta - Steven Deverel; Paul Jacobs; Christina Lucero; Sabina Dore; T. Rodd Kelsey (eScholarship Publishing, University of California, 2017)
doi: https://doi.org/10.15447/sfews.2017v15iss3art2We quantified the greenhouse-gas (GHG) emission and economic implications of alternative crop and wetland mosaics on a Sacramento–San Joaquin Delta island: Staten Island. Using existing GHG fluxes measurements for the Delta and biogeochemical models, we estimated GHG emissions for a range of scenarios, including the status quo, modified groundwater management, and incorporating rice and managed wetlands. For current land uses, emissions were predicted to vary greatly (48,000 to 105,000 t CO2-e yr−1) with varying groundwater depth. GHG emissions were highest when water depth was 120 cm, the typical depth for a Delta island, and lowest if water table depth was shallowest (60 cm). In the alternate land-use scenarios, we simulated wetlands and rice cultivation in areas of highest organic-matter soils, greatest subsidence, and GHG emissions. For each scenario, we analyzed economic implications for the land-owner by determining profit changes relative to the status quo. We spatially assigned areas for rice and wetlands, and then allowed the Delta Agricultural Production (DAP) model to optimize the allocation of other crops to maximize profit. The scenario that included wetlands decreased profits 79% relative to the status quo but reduced GHG emissions by 43,000 t CO2-e yr−1 (57% reduction). When mixtures of rice and wetlands were introduced, farm profits decreased 16%, and the GHG emission reduction was 33,000 t CO2-e yr−1 (44% reduction). When rice was cultivated on 38% of the island, profit increased 12% and emissions were 22,000 t CO2-e yr−1 lower than baseline emissions (30% reduction). Conversion to a mosaic of wetlands and crops including rice could substantially reduce overall GHG emissions of cultivated lands in the Delta without greatly affecting profitability.